Determinant Islamic Banking Financing during COVID-19 Pandemic - Deni Lubis; Dita Puspitasari; Qoriatul Hasanah (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2022)
The spread of COVID-19 is becoming one of the biggest threats to the global economy and financial markets in the world. This study is conducted to determine the effect of the factors that influence profit-sharing financing during the COVID-19 pandemic on Islamic banking in Indonesia. This study uses a sample of 13 Islamic Commercial Banks and 20 Sharia Business Units and the time period is quarter I-IV 2020. The analytical tool used in this study is panel data regression with the Random Effect Model (REM) approach. The results indicate that DPK, NPF, FDR, ROA, GDP, inflation and the money supply simultaneously has an effect on profit sharing financing. For the partial estimation results, the variables of DPK, FDR, and ROA have a significant and positive effect on profit sharing financing. While the variables of NPF, GDP, inflation, and the money supply have no significant effect on profit sharing financing.